PENGEMBANGAN MODUL BIOLOGI MATERI KEANEKARAGAMAN HAYATI BERBASIS POTENSI LOKAL UNTUK SISWA KELAS X SMA DI XIII KOTO KAMPAR - Fitri Juliana; Nursal Nursal; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is a descriptive research that aims to produce learning module for students class x hight school. The subject of this research is competency the basis (KD) 3.2 hight school class x : the analyze various levels of biodiversity in Indonesia along with the threat preservation. Research conducted at FKIP Riau University and SMAN 1 XIII Koto Kampar in September to November 2017. This research is a development research with ADDIE model (Analyze, Design, Develop, Implement and Evaluate) and just made to the stage of development. Data collection begins with local biodiversity observations of spesies (plant and animals), which are widely present around student learning environments, including the diversity of gene, species, and coomunitas/ecosystem levels. Data observations biodiversity based local potential will be used to design a learning modules biodiversity. Further data was collected by the validation and trial. Validation aims to see useful module from expert opinion in the field of material of the existing in learning modules. While the trial aims to see useful module to analyze the questionnaire students’ responses. Data obtained from the analysysis of the results obtained a score all modules obtain an average score 4.33 by category is invalid. Consists of aspects of the content presented obtain an average 4.46 by category very valid, aspacts of the languege obtained averange score of 4.23 by category very valid, and aspacts graphics design obtain ab average score of 4.33 by category is invalid. Average value response 20 students to the module developed on learning 1 is 4.24, learning 2 average score of 4.20, and at the learning modules 3 ie with an average score of 4.24 by category very good.Keywords: Research Development, Learning Modules, Biodiversity Potential Local.